TRANSLATION OF THE RELATIONAL VALUES OF EUPHEMISTIC EXPRESSIONS INTO ENGLISH FROM INDONESIAN LITERARY WORK - Ahdi Riyono; Emzir Emzir; Ninuk Lustyantie (University of Kuningan, 2019)
This research is to describe the forms and translation techniques of Euphemism in the rendering of The Dancer novel by René TA Lysloff. The researcher used a qualitative method with a content analysis technique. The Data of research are in the forms of clauses containing expressions of Euphemism. The data source was taken from Ronggeng Dukuh Paruk (RDP) novel and its translation of the Dancer. The result showed that there were 35 data (83.3%) of the Euphemism forms of translated into euphemisms, and only 7 data (16,7%) of euphemisms were translated into other forms. The techniques used include single, duplet, and triplet techniques. The conclusions of the research showed that there were shifts in ideological forms and values of the translated novel.